Operator Theory Recent Advances, New Perspectives and Applications - Abou Jaoudé, Abdo (IntechOpen, 2023)
Operator theory is a fascinating model that includes essential theorems and diverse applications in all science. This book discusses some fundamental aspects of pure and applied operator theory and the use of the theory to solve a large array of problems. As such, it will be of interest to scholars, researchers, and undergraduate and graduate students in pure and applied mathematics, classical and modern physics, engineering, and science in general.